Box–Behnken experimental design for zinc borate Zn2_x000D_ B6_x000D_ O11·7H2_x000D_ O - SAYAN, PERVİZ; POLAT, SEVGİ (My University, 2020)
The present study investigated the effect of the operating conditions on thecrystallization of zinc borate. For zinc borate crystallization, sodium tetraboratedecahydrate and zinc sulfate heptahydrate were used as reactants. In thefirst part of the study, the crystals were characterized by X-ray diffractionspectroscopy (XRD), Fourier-transform infrared spectroscopy (FTIR), lightmicroscopy, and particle size and thermogravimetric analysis. The resultsshow that the obtained crystals were in the form of Zn2B6O11·7H2O, and theoperating conditions had a significant effect on the size, morphology, andfiltration characteristics of the zinc borate crystals. In the second part ofthe study, Box–Behnken design (BBD) with response surface methodology(RSM) was employed to determine the optimal operating conditions for zincborate crystallization. The effects of stirring rate, temperature, and reactantfeed rate on the average particle size were investigated. The results show thatthe data sufficiently fit the second-order polynomial model. The crystallizationconditions, including stirring rate, temperature, and reactant feed rate, werestudied at 400–500 rpm, 45–85 ºC, and 300–900 mL/h, respectively. Theminimum particle size (3.3 µm) was obtained at a stirring rate of 450 rpm, atemperature of 85 ºC, and a reactant feed rate of 300 mL/h.